Environmental Characterization of Underwater Munitions Constituents at a Former Military Training Range. (20th July 2021) - Rosen, Gunther; Lotufo, Guilherme R.; Belden, Jason B.; George, Robert D.
Abstract: As a result of military activities, unexploded ordnance and discarded military munitions are present in underwater environments, which has resulted in the release of munitions constituents including the high explosives 2, 4, 6‐trinitrotoluene (TNT) and hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX), along with their primary degradation products, to the water column and adjacent sediments. The present study focused on the characterization of underwater exposure and concentrations of energetics such as TNT and RDX at the former Vieques Naval Training Range at Bahia Salina del Sur (Vieques, Puerto Rico, USA), a bay with documented high incidence of munitions. In situ passive sampling using polar organic chemical integrative samplers (POCIS) was used for the detection and quantification of constituents in water at target locations approximately 15 to 30 cm from 15 individual potentially leaking munitions, and also at 15 unbiased locations approximately evenly spaced across the Bay. For comparison with POCIS‐derived concentrations, grab samples were taken at the POCIS target locations. The POCIS‐derived and averaged grab samples agreed within a factor of 3. When detected, munitions constituent concentrations (primarily TNT and RDX) were observed at ultratrace concentrations (as low as 4 ng/L for RDX), except 30 cm from one General Purpose bomb where the TNT concentration was 5.3 µg/L, indicating that low‐level contamination exists at Bahia Salina del Sur on a very localized scale despite the relatively high density of munitions, similar to previously reported results for other munitions sites around the world. Sediment and porewater sampled at 4 stations where munitions constituents were detected in the water column had concentrations below detection (approximately 5 µg/kg and 5 ng/L, respectively), suggesting that the sediment was not a sink for these constituents at those locations. Environ Toxicol Chem 2022;41:275–286. © 2021 SETAC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Abstract : Polar organic chemical integrative sampler placed adjacent to a 500‐lb General Purpose bomb, potentially containing munitions constituents (e.g., 2, 4, 6‐trinitrotoluene, hexahydro‐1, 3, 5‐trinitro‐s‐triazine), at Vieques, Puerto Rico, USA.